Selective‐area growth of doped GaN nanorods by pulsed‐mode MOCVD: Effect of Si and Mg dopants. Issue 8 (10th April 2017) - Bae, Si‐Young; Lekhal, Kaddour; Lee, Ho‐Jun; Min, Jung‐Wook; Lee, Dong‐Seon; Honda, Yoshio; Amano, Hiroshi
Abstract : Injecting current with a uniform carrier concentration is important for applications with three‐dimensional architectures such as vertical power devices or displays. In III‐nitride nanostructures, dopants not only incorporate differently depending on the surface orientation but can also seriously affect the kinetic equilibrium shapes of the nanorods. Herein, we report selective‐area growth of doped GaN nanorods grown by pulsed‐mode metalorganic chemical vapor deposition. Two dopants, Si and Mg, were employed as donor and acceptor atoms, respectively, for a mono‐doping approach. Furthermore, a mixed flow of Si and Mg was supplied for a co‐doping approach. We compared the morphological effects and growth rates of each doped GaN nanorod array. Then, we proposed appropriate growth mechanisms for the doped GaN nanorods on the basis of our structural characterizations. These results might extend the morphological functionality of GaN nanorods by including doping and may also provide an appropriate foundation for the design of nanostructure‐based electronic or photonic devices.